Pattern recognition and machine intelligence : 7th International Conference, PReMI 2017, Kolkata, India, December 5-8, 2017, Proceedings /: 7th International Conference, PReMI 2017, Kolkata, India, December 5-8, 2017, Proceedings. (2017) - Unknown
No abstract available